Alternative Disinfection Methods Use to Control of Microbial Quality and Shelf-life of Raw Eaten Vegetables (Case Study) - Pourzamani 1, Hamidreza; Kadkhodaei 2, Narges; Fadaei 2, Saed; Taheri 1,2, Ensiyeh; Bagheri 2, Reyhaneh; Mohammadi Manesh3, Reza; yusefi 4, Hosein; Hatamzadeh, Maryam; Majidi 6, Saba; Nahidan 2*, Maedeh (Shahroud Journal of Medical Sciences, 2019)
Background: Fresh-cut vegetables are particularly susceptible to microbial growth and, therefore, the use of an effective sanitizer on this product is great importance. Method: The common vegetable types obtained from a local wholesale market in Isfahan and washed with different common disinfectants such as edible salt, sodium hypochlorite, electrolyzed water (EW), complex disinfectant, calcium hypochlorite, and dishwashing liquid. Disinfection time and concentration select according to the Official Protocol in Iran. A total of 126 samples including Mint, Savory, parsley, Garden cress, Common Purslane, Chives, Basil, Radish, and mixed vegetables were analyzed for total bacteria, total coliform bacteria, and E. coli. Result: Results demonstrated that calcium hypochlorite has the best efficiency for total coliforms in separate vegetable of parsley, Garden cress, Common Purslane, Chives, Radish, with100% efficacy. For total coliforms BGB (Brilliant Green Broth) test, complex disinfectant and calcium hypochlorite have 100% removal for all of the vegetables. E.coli test result showed in four vegetables not E.coli but for another vegetable except Dishwashing Liquid efficiency was 100%. Among all disinfectants, EW has a high efficiency for mixed vegetables. For Basil disinfected with edible salt and mint washing with complex disinfectant, Eimeria parasite and in savory disinfected with calcium hypochlorite Hook worm parasitic was found. Shelf-life was between 1 to 5 days. Conclusion: Our research suggested that EW has a good effect for total coliforms, fecal coliforms, E.Coli, and helmet eggs removal, also save the vegetable shelf life.